2022
DOI: 10.3233/adr-210061
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Cholinesterase Inhibitors: Current Scenario in Therapies for Alzheimer’s Disease and Future Perspectives

Abstract: Alzheimer’s disease (AD) is a slowly progressive neurodegenerative disease conceptualized as a continuous process, ranging from mild cognitive impairment (MCI), to the mild, moderate, and severe clinical stages of AD dementia. AD is considered a complex multifactorial disease. Currently, the use of cholinesterase inhibitors (ChEI), such as tacrine, donepezil, rivastigmine, and galantamine, has been the main treatment for AD patients. Interestingly, there is evidence that ChEI also promotes neuroprotective effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 160 publications
0
24
0
1
Order By: Relevance
“…The efficacy of each of them has been extensively studied in several studies, both in animal models and clinical trials. Its use has shown that it has a beneficial effect in all stages of the disease and could also have a neuroprotective effect by increasing cell viability and reducing neuronal death, as well as the presence of inflammatory mediators [ 225 , 226 ].…”
Section: Therapymentioning
confidence: 99%
“…The efficacy of each of them has been extensively studied in several studies, both in animal models and clinical trials. Its use has shown that it has a beneficial effect in all stages of the disease and could also have a neuroprotective effect by increasing cell viability and reducing neuronal death, as well as the presence of inflammatory mediators [ 225 , 226 ].…”
Section: Therapymentioning
confidence: 99%
“…One major limitation derives from the fact that some therapeutic interventions focus only on one aspect of the disease, such as limiting the neuroinflammation [ 19 ] or modulating the cholinergic system [ 20 ]. Indeed, anticholinergic drugs such as Donepezil and Galantamine are among the first approved and still in-use medications in the daily clinical practice [ 21 ]. Memantine, an N-methyl-D-aspartate (NMDA) receptor blocker, one of the most frequently prescribed medications in the United States, is administered alone or in combination therapy in moderate-to-severe AD patients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, in the brains of AD patients, the activity of AChE remains unchanged or declines ( Kumar et al, 2018 ; Karthika et al, 2022 ). Currently available synthetic acetylcholinesterase inhibitors, including galanthamine, rivastigmine, donepezil, and tacrine, have been clinically used for AD treatment ( Moreira et al, 2022 ). However, these drugs have therapeutic activity along with side effects such as short duration of biological action, gastrointestinal disturbance, low bioavailability, and hepatotoxicity ( Reza et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%